Faktorâ€Faktor Organisasional Sebagai Pencetus Kecenderungan Agresi di Tempat Kerja : Studi Metaanalisis - Harsanti, Intaglia (Jurnal Psikologi, 2009)
This article presented a metaâ€analysis of the experimental and survey literature that has examined the correlation between organizational factors and workplace aggression. The metaanalysis reviewed 31 studies from 20 articles. The results indicated that there is a correlation between organizational factors and workplace aggression.This analysis extended previous work by directly correcting error of sampling and measurements. The results showed that organizational factors have been identified as a predictor of the workplace aggression.